Kinerja Umkm, Kemiskinan Dan Ketimpangan Pendapatan: Bukti Data Panel Kabupaten Kota Di Provinsi Jambi - Amri, Khairul; Dian Fitri, Cut (Brida Provinsi Jambi, 2024)
This study analyzes the effect of MSMEs performance on poverty rates and income inequality in Jambi province. Using panel data from 11 regencies/cities during the period 2013-2022, the analysis model applied to estimate the functional relationship between variables is a fixed effect panel regression approach. The results of the study indicate that MSMEs performance can positively and significantly reduce poverty rates and improve income distribution in the region. The higher the performance of MSMEs, the lower the poverty rate and the lower the income inequality. This finding has implications that local government efforts to reduce poverty rates and improve income distribution in the province can be carried out through policies related to improving MSMEs performance